Cynthia Ozick's fiction : tradition & invention - Kauvar, Elaine M. (Elaine Mozer), 1939- (Jewish literature and culture., 1993)
Cynthia Ozick's emphasis on tradition has made her, paradoxically, one of the most innovative writers of our time. Elaine M. Kauvar illuminates the intricacies of Ozick's texts, explores the dynamics of her creativity, and excavates her sources, contexts, and allusions. She provides readings of all of Ozick's fiction, from her first published novel, Trust, through The Messiah of Stockholm. Working chronologically, Kauvar traces the development of the storyteller's thought and art, examines the themes that pervade Ozick's tales - the battle between Hebraism and Hellenism, the lure of paganism and the dangers of idolatry, the implications and consequences of assimilation, the perplexities of the artist and the besetting dangers of art - and demonstrates the dialectic existing between her tales, their shifting perspectives, and competing ideas. Precisely because Ozick draws on the resources in her heritage, Kauvar concludes, she transcends narrow categories and defies rigid ideologies.